In-situ restructuring of Ni-based metal organic frameworks for photocatalytic CO2 hydrogenation - Abdelaziz Gouda; Karen Hannouche; Abhinav Mohan; Chengliang Mao; Ehsan Nikbin; Alexandre Carrière; Jessica Ye; Jane Y. Howe; Mohini Sain; Mohamad Hmadeh; Geoffrey A. Ozin (Nature Communications)
Abstract As the global quest for sustainable energy keeps rising, exploring novel efficient and practical photocatalysts remains a research and industrial urge. Particularly, metal organic frameworks were proven to contribute to various stages of the carbon cycle, from CO2 capture to its conversion. Herein, we report the photo-methanation activity of three isostructural, nickel-based metal organic frameworks incorporating additional niobium, iron, and aluminum sites, having demonstrated exceptional CO2 capture abilities from thin air in previous reports. The niobium version exhibits the highest performance, with a CO2 to CH4 conversion rate in the order of 750–7500 µmol*gcatalyst −1*h−1 between 180 °C and 240 °C, achieving 97% selectivity under light irradiation and atmospheric pressure. The in-depth characterization of this framework before and after catalysis reveals the occurrence of an in-situ restructuring process, whereas active surface species are formed under photocatalytic conditions, thus providing comprehensive structure-performance correlations for the development of efficient CO2 conversion photocatalysts.